Economic Benefits and Risk of Delay Selling Robusta Coffee (Coffea Canephora) In Central Island Village, Jangkat District, Merangin District - Ainil Fatimah; Asminar Asminar; Widuri Susilawati (International Journal of Ecma Science, 2021)
Robusta coffee is a type of coffee plant with the scientific name Coffea canephora. The research objective was to analyze the benefits obtained by coffee farmers, to determine the price risk faced by coffee farmers who delayed selling, to identify problems faced by coffee farmers, to analyze factors that influenced coffee farmers' decisions to delay selling, and to determine economic benefits. received by coffee farmers who delayed selling in Pulau Tengah Village, Jangkat District, Merangin Regency. The choice of location in Pulau Tengah Village as the object of research was carried out purposively (deliberately) by considering that Pulau Tengah Village is a production center for coffee plantations in Jangkat District (Jangkat 2019 District). This research was conducted from December 30, 2019, to January 30, 2020. The data analysis method used in this study, namely the descriptive method, is a method used to describe a research result. Where data was collected descriptively through questionnaires. The results showed that the coffee farmers in Pulau Tengah Village, Jangkat District, Merangin Regency received a profit of Rp. 78,473,628 / year. The price risk faced by coffee farmers who delay selling in Pulau Tengah Village, Jangkat District, Merangin Regency has a low risk (CV) of 0.003. The problems faced by farmers who delay selling in Pulau Tengah Village, Jangkat District, Merangin Regency are price uncertainty, how to deal with shrinkage levels, pest attacks, and fulfillment of needs. The factors that influence the farmers' decision to postpone selling in Pulau Tengah Village, Jangkat District, Merangin Regency are price, income, and production as well as the economic benefits received by farmers who postpone selling in Pulau Tengah Village, Jangkat District, Merangin Regency, in the form of a selling price difference of Rp.1.376.62 / kg.